PROFESSIONAL ETHICS AND LEGAL PROTECTION FOR NOTARY - Soegianto Soegianto (UNISSULA, 2019)
Notary is a profession that is authorized to make authentic deeds about all deeds, agreements and stipulations required by a general regulation or by the interested parties to be stated in an authentic deed, guarantee the certainty of the date, keep the deed and give the grosse, copies and quotations. Basing on the moral and ethical values of the Notary, carrying out the position of the Notary Public is a service to the community (client) independently and not taking sides in the field of notary, whose service is lived as a vocation based on the spirit of devotion to fellow human beings for the public interest and rooted in respect for dignity humans in general and notary dignity in general. In exercising its authority as a Public Official who makes an authentic deed, the Notary Public must uphold the Notary Ethics Code and be protected by Act Number 2 of 2014 amending the Law Number 30 of 2004 concerning the Position of Notary.